MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI MODEL MIND MAPPING PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SDN RAPPOKALLING 67/1 - Chairul Agung Tunny; Abdul Azis; Rismawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Chairul Agung Tunny, 2025. Enhancing Students’ Motivation and Learning Outcomes Through the Mind Mapping Model in Pancasila Education at SDN Rappokalling 67/1, Makassar City. Undergraduate Thesis, Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisors: Abdul Azis and Rismawati. This research aims to improve students’ motivation and learning outcomes in the subject of Pancasila Education by applying the mind mapping learning model in Class V of SDN Rappokalling 67/1, Makassar. The study was conducted in response to the low motivation and learning results among students, which were attributed to unengaging, teacher-centered teaching methods. The method used was Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of four stages: planning, implementation of action, observation, and reflection. Instruments used in the research included learning motivation observation sheets and tests for learning outcomes. The results showed that the mind mapping model had a positive impact on student motivation. In the first cycle, 18 students were categorized as having